2013
DOI: 10.1080/09084282.2012.753074
|View full text |Cite
|
Sign up to set email alerts
|

Cognate Effects and Executive Control in a Patient with Differential Bilingual Aphasia

Abstract: We describe a case study of a French-Dutch bilingual patient with differential aphasia, showing clearly larger impairments in Dutch than in French. We investigated whether this differential impairment in both languages was due to selective damage to language-specific brain areas resulting in the "loss" of the language representation itself, or rather if it reflects an executive control deficit. We assessed cross-linguistic interactions (involving lexical activation in the most affected language) with cognates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 50 publications
6
46
0
1
Order By: Relevance
“…During each period of treatment, the patient received naming rehabilitation in one language, and we examined within-language generalization and cross-language generalization to translation equivalents and semantically related items. This patient was also administered the Cognitive Linguistic Quick Test (Helm-Estabrooks, 2001) and a nonlinguistic flanker task as part of her overall language assessment to examine broader cognitive control abilities (Green et al, 2010;Verreyt et al, 2013).…”
Section: Aims Of the Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…During each period of treatment, the patient received naming rehabilitation in one language, and we examined within-language generalization and cross-language generalization to translation equivalents and semantically related items. This patient was also administered the Cognitive Linguistic Quick Test (Helm-Estabrooks, 2001) and a nonlinguistic flanker task as part of her overall language assessment to examine broader cognitive control abilities (Green et al, 2010;Verreyt et al, 2013).…”
Section: Aims Of the Current Studymentioning
confidence: 99%
“…Based on Abutalebi and Green's model, the nonlinguistic executive mechanism is likely to be important in limiting cross-language interference and thereby facilitating cross-language treatment generalization. There are several reports of bi/multilingual patients with language and cognitive control difficulties (Green et al, 2010;Kong, Abutalebi, Lam, & Weekes, 2013;Nilipour & Ashayeri, 1989;Verreyt, De Letter, Hemelsoet, Santens, & Duyck, 2013), although their findings have rarely been interpreted within the framework of the neurocognitive model (Kong et al, 2013). Likewise, while there are treatment studies that have examined the issue of cognitive control in rehabilitation (e.g., Goral et al, 2013), the only paper to examine changes in cognitive control as a function of rehabilitation is by Abutalebi et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…An earlier evaluation (e.g., at acute or subacute phase) following the stroke could have better shown whether this so-called pathological fixation on L2 and the L1 impairment has resulted from impairment in cognitive control function. Verreyt et al [14] reported the case of an early French-Dutch bilingual aphasic who, following a lesion to the left thalamus, presented larger impairment in Dutch. By showing cognate facilitation and cognate interference effects in different lexical decision tasks and an impaired performance in the flanker task, the authors suggested that the differential pattern of impairment in language could be explained by a language-control deficit.…”
Section: Introductionmentioning
confidence: 99%
“…The higher outlier rate for PWDA compared with the other groups is consistent with the finding that RTs are highly variable in PWDA (Verreyt et al . , Lalor and Kirsner ). We included a random slope for Cognate status into the model on RT data, because maximum likelihood modelling supported the conclusion, χ 2 (2) = 14.82, p < .001.…”
Section: Resultsmentioning
confidence: 92%
“…As in other studies examining bilingual aphasia, only the results based on ACC will be interpreted because of the very high variability typically observed on RTs for PWDA (Lalor and Kirsner , Verreyt et al . ). The results on RTs on both tasks are nevertheless reported for completeness.…”
Section: Resultsmentioning
confidence: 97%